Trust in the U.S. Government and Its Health Agencies in the Time of COVID-19 - Maraika Geisterfer-Black; Taylor Niemi; Leonie Neier; Victor G. Rodwin (MDPI AG, 2022)
This article examines the factors affecting Americans' trust in their federal government and its health agencies during the COVID-19 public health crisis. More specifically, we examine the evolution of Americans' trust in their government and health system and how, in the context of the COVID-19 pandemic response, it has been affected by multiple factors. Several academic journals, government policy recommendations and public health polls were evaluated to understand the public's trust in the federal government and its health institutions. Public trust in institutions during a global pandemic is essential in influencing adherence to a pandemic response (both non-pharmaceutical and medical interventions). Americans' trust in institutions is built and maintained by a variety of factors. We focus on: political polarization and involvement, media influence and health communications, history of systemic racism and socioeconomic inequalities, and pandemic fatigue. Based on the interplay of these factors, we conclude with recommendations for future pandemic response strategies.